ANALISIS KINERJA KEUANGAN PT. TIMAH, TBK PERIODE 2016 - 2020 - Mohamad Makrus (LPPM STIE PERTIBA Pangkalpinang, 2021)
The company's financial performance is one measure of the company's success in an accounting period. One of the measures to assess financial performance is by using financial statement analysis. With a view to knowing the financial performance of PT. Timah Tbk. during 2016 to 2020, in this study the researchers used several financial statement analysis tools. The use of secondary data comes from the official website of the Indonesian stock exchange at the address https://www.idx.co.id/corporate-tercatat/laporan-keuangan-dan-tahun/, to retrieve financial data such as annual financial report data from 2016 to 2015. /d 2020. Quantitative descriptive analysis techniques using comparative financial statement analysis (comparative profit and loss and comparative balance) and financial statement ratio analysis consisting of (a) short-term liquidity, (b) capital structure and solvency, (c) returns on investment capital, (d) asset turnover, and (e) operating performance and profitability. The results showed that the net profit of PT. Timah Tbk. in 2016, 2017, and 2018 on a year-on-year (yoy) basis, with the previous year, generally experiencing an increase, but in 2019 and 2020 experiencing a decline. Financial performance of PT. Timah Tbk. seen from the net profit margin sequentially from 2016 to 2020 experienced fluctuations and the highest achievement was in 2017 and the lowest was in 2019. While the assets of PT. Timah Tbk. in 2016, 2017, 2018, and 2019 on a year-on-year (yoy) basis, with the previous year, generally experiencing an increase, but in 2020 it experienced a decline. Liabilities/debts of PT. Timah Tbk., in 2016 to 2020 on a year on years (yoy) basis with the previous year, in general, experiencing fluctuations. Equity/capital of PT. Timah Tbk., in 2016, 2017, and 2018 years on years (yoy) with the previous year in general increasing, but in 2019 and 2020 experiencing a decline